2014
DOI: 10.4161/cc.28255
|View full text |Cite
|
Sign up to set email alerts
|

Senescence-accelerated OXYS rats: A model of age-related cognitive decline with relevance to abnormalities in Alzheimer disease

Abstract: Senescence-accelerated OXYS rats are an experimental model of accelerated aging that was established from wistar stock via selection for susceptibility to cataractogenic effects of a galactose-rich diet and via subsequent inbreeding of highly susceptible rats. Currently, we have the 102nd generation of OXYS rats with spontaneously developing cataract and accelerated senescence syndrome, which means early development of a phenotype similar to human geriatric disorders, including accelerated brain aging. in rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
69
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 101 publications
(134 reference statements)
11
69
1
Order By: Relevance
“…9 Moreover, SkQ1 increases the aB-crystallin level and decreases the Ab level in the retina (manuscript in preparation) as well as in the brain. 40 These findings are consistent with the present study and support the view that aB-crystallin is involved in degeneration of the retina.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…9 Moreover, SkQ1 increases the aB-crystallin level and decreases the Ab level in the retina (manuscript in preparation) as well as in the brain. 40 These findings are consistent with the present study and support the view that aB-crystallin is involved in degeneration of the retina.…”
Section: Discussionsupporting
confidence: 83%
“…39 Recently, we showed that Ab accumulates with age in the retina and in the brain of OXYS rats; 22,40 however, the level of Ab is not elevated at the early stages of retinopathy, that is, at the age of 3 months. 22 The Ab level increases in the retina of middle-aged and old OXYS rats, when these rats present with severe stages of the disease accompanied by pronounced neurodegenerative changes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our group showed that OXYS rats exhibit signs of AD-like pathology; in particular, amyloid-b accumulates in the hippocampus and cortex of OXYS rats with age, although substantial amyloid-b accumulation occurs only at 13 months of age (Stefanova et al 2014a). Thus, in OXYS rats, the alterations of melatonin secretion occur before accumulation of amyloid-b.…”
Section: Discussionmentioning
confidence: 97%
“…OXYS rats are characterized by progressive age-related aggregation of amyloid-b and hyperphosphorylation of the tau protein as well as mitochondrial dysfunction, loss of synapses, neuronal death, and ultimately cognitive decline (Stefanova et al 2010(Stefanova et al , 2011(Stefanova et al , 2014a. We demonstrated previously that the signs of accelerated aging of the brain in OXYS rats develop simultaneously with changes in the metabolism of the neurotransmitter serotonin in the brain regions that are essential for learning and memory (Shcheglova et al 2002).…”
Section: Introductionmentioning
confidence: 93%
“…[1][2][3][4] This research often involves transgenic or knockout rodent lines for the analysis of a specific gene, protein, or phenotype. For these studies, it is useful to correlate age, genetic alterations, or therapeutic interventions with changes in molecular markers of aging.…”
Section: Introductionmentioning
confidence: 99%